Metode Menghafal Al Qur’an pada Anak Usia Sekolah Dasar di SDI Al Munawwarah Pamekasan - mego, dian (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
This article describes the method of memorizing the Qur’an in SDI Al Munawwarah Pamekasan. Parents who want to provide the best education oriented to this article describe the method of memorizing the Qur’an in SDI Al Munawwarah Pamekasan. The desire of parents who want to provide the best education oriented to the Qur’an makes educational institutions offer a variety of learning methods. The need to learn the Qur’an is one of the factors in the emergence of various educational educational institutions that help students learn the Qur’an and memorize it. SDI Al Munawwarah is one of the educational institutions that offers the Hifdzil Qur’an program with the Qazmumethod. In this study, using a descriptive qualitative approach because researchers only analyze the implementation of learning and memorizing the Qur’an at elementary school age. There are methods that can help the students memorize the Qur’an well through the Qazmu method. It is hoped that through this method students can become a generation of believers and pious and always love the Qur’an.